Lipid Membrane-Selective Interactions Driven by Nanosilver Anisotropy Insights from Prokaryotic and Erythrocyte Models - Pistonesi, Denise B (Langmuir : the ACS journal of surfaces and colloids, 2025)
The increasing use of silver nanoparticles (AgNPs) in medical applications highlights the need for thorough studies of their health effects, particularly at the cellular level. Due to the complexity of replicating real cell membranes, Langmuir monolayers (LMs) are employed as simplified models of the initial biological barrier. These systems allow for controlled conditions to investigate molecular behavior at the membrane interface, offering insights into the fundamental mechanisms involved. In this research, we explore the effects of the shape and electronic anisotropy of AgNPs on bacterial and erythrocyte membrane models using dipalmitoylphosphatidylcholine (DPPC) and DPPC/cholesterol (CHOL) combinations. The interaction between the lipids and silver nanoparticles was investigated using film balance measurements by analyzing surface pressure (π-A) and membrane potential (ΔV-A) isotherms. These measurements were complemented by X-ray reflectometry to obtain detailed structural information at the interface. Additionally, in vitro experiments were conducted to provide a behavioral profile of the nanoparticles' effects, linking physicochemical interactions with cellular responses. Our findings demonstrate that the shape anisotropy of prism-like silver nanoparticles (p-AgNPs) significantly impacts membrane structural integrity and mechanical properties, with the extent of these effects depending on membrane composition and cholesterol content. Prism-like silver nanoparticles interact more strongly with DPPC monolayers than spherical nanoparticles (s-AgNPs), inducing higher surface pressure and a decrease in membrane rigidity due to lipid extraction. In DPPC/CHOL monolayers, p-AgNPs promote CHOL microdomain formation and disrupt DPPC organization, with these effects becoming more pronounced at higher CHOL concentrations. Prism-like nanosilver also enhances lipid extraction and membrane permeability in bacterial-like membranes, while in erythrocyte-mimetic membranes, it disrupts membrane organization and reduces rigidity, with cholesterol modulating this impact. These results suggest that p-AgNPs exhibit potent antibacterial properties but also pose risks of destabilizing eukaryotic cell membranes. Overall, the study explores the concentration-dependent antibacterial and cytotoxic effects of p-AgNPs, highlighting how their morphological anisotropy plays a decisive role in modulating nanoparticle/membrane interactions. By uncovering specific mechanisms at the bionano interface, this work sets an important precedent for the rational design of nanosilver-based devices and treatments, contributing valuable knowledge to the safe and effective application of anisotropic nanomaterials in biomedicine